2000
DOI: 10.1902/jop.2000.71.3.438
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Combined Oral Treatments With Cyclosporine A and Nifedipine or Diltiazem on Drug‐Induced Gingival Overgrowth in Rats

Abstract: These results suggest that gingival overgrowth is induced in rats as a side effect of CsA, nifedipine, or diltiazem, and the combined use of these drugs influences rat growth, blood drug levels, and the severity of gingival overgrowth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
21
1
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 30 publications
5
21
1
1
Order By: Relevance
“…In fact, the fi ndings of previous investigations have shown that the administration of diltiazem in the doses used in the present study did not induce toxicity and that the treatment was well supported by the animals. 8,13,16,17 Macroscopically, the sucrose-rich diet induced dental biofi lm accumulations in all animals though none of them exhibited clinical characteristics of gingival overgrowth, which confi rms our previous fi ndings. 8 However, Morisaki et al 16 (2000) observed gingival overgrowth in rats after administration of diltiazem in doses greater than those used in the present study during a similar experimental period.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In fact, the fi ndings of previous investigations have shown that the administration of diltiazem in the doses used in the present study did not induce toxicity and that the treatment was well supported by the animals. 8,13,16,17 Macroscopically, the sucrose-rich diet induced dental biofi lm accumulations in all animals though none of them exhibited clinical characteristics of gingival overgrowth, which confi rms our previous fi ndings. 8 However, Morisaki et al 16 (2000) observed gingival overgrowth in rats after administration of diltiazem in doses greater than those used in the present study during a similar experimental period.…”
Section: Discussionsupporting
confidence: 86%
“…8,13,16,17 Macroscopically, the sucrose-rich diet induced dental biofi lm accumulations in all animals though none of them exhibited clinical characteristics of gingival overgrowth, which confi rms our previous fi ndings. 8 However, Morisaki et al 16 (2000) observed gingival overgrowth in rats after administration of diltiazem in doses greater than those used in the present study during a similar experimental period. Microscopically, there was only a mild infl ammation in the animals (Figure 1), which is particularly relevant because the diet followed by the animals was expected to cause gingivitis.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Nos pacientes em uso de associação medicamentosa a presença de 70,8% de indivíduos com comprometimento gengival foi comparável àquela da maioria dos estudos relatados na literatura 16,19,27,34,37 . Nesses relatos, a associação dessas drogas provocou acometimento gengival geralmente mais intenso e 0,23 a 5,38 vezes mais freqüentes do que entre os que usaram somente a ciclosporina, sendo atribuída ao emprego de nifedipina em 15% a 44% dos usuários 25,38,39,40,41 . As diferenças observadas na freqüência de acometimento gengival podem ser imputadas à variação no sistema de avaliação.…”
Section: Discussionunclassified
“…Twenty-four 15-day-old, specifi c pathogen-free, male Fischer rats were purchased with their lactating dams from Charles River Japan and reared in a clean room at 25 ° C in the animal facility of Osaka University Graduate School of Dentistry. The animal experiment was performed basically according to the method of Morisaki et al [18,19] . Briefl y, the rat pups were divided into 4 groups (6 rats/group) for the experimental period of 41 days.…”
Section: Animals and Drug Administrationmentioning
confidence: 99%